Challenges in Diagnosis and Management of Spontaneous Coronary Artery Dissection in a Young Patient - Beatriz J. S. Branco; Cesar Sanchez; Cesar Mendoza; Michael Magarakis; Alejandro Eric Macias; Tomas A. Salerno (Brazilian Journal of Cardiovascular Surgery, 2019)
Abstract Spontaneous coronary artery dissection (SCAD) is characterized by tear of the inner layer in the coronary artery, creating a false lumen between the inner and central layer. Its infrequent incidence often leads to delay in diagnosis posing challenges in management. There are currently no guidelines for the treatment of this condition. We describe an adult patient who presented with multiple episodes of ventricular fibrillation, in whom cardiac catheterization showed SCAD, treated by off-pump coronary artery bypass.